Proyecto de inversión y desarrollo para aireadores y comederos automáticos para el sector camaronero del cantón Durán - Ramírez Chalén, Víctor (2019)
At present the aquaculture sector, the shrimp farmers that in their productive processes sow at high densities, being the biggest problem the oxygen dissolved in the water that in many occasions are factors of losses in the shrimp business, which constitutes a limitation at the moment of have a higher biomass and the production is affected therefore the profitability of the company, the producers are betting on the feeding system, combining with models to oxygenate the water of the pools, so it seeks to counteract these events by installing aerators in the pools that will help oxygenate the water and increase the survival of the shrimp. In this investigation the descriptive method was applied, this technique is developed with two qualitative and quantitative approaches. The purpose of the research topic is to analyze the feasibility of the investment plan in the acquisition of aerators and feeding systems and to verify the improvement in the productive field to provide information and an economic analysis of the advantages in the increase productive yields. The Financial Analysis, in order to see the feasibility and viability of it, will be done through………